Bioremediation potential of rhizosphere bacterial consortium in lead (Pb) contaminated rice plants - MOHAMMAD UBAIDILLAH; NURHALIZA THAMRIN; FADIA INTAN CAHYANI; DINA FITRIYAH (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Ubaidillah M, Thamrin N, Cahyani FI, Fitriyah D. 2023. Bioremediation potential of rhizosphere bacterial consortium in lead (Pb) contaminated rice plants. Biodiversitas 24: 4566-4571. Lead (Pb) is one of the toxic heavy metals detected in various chemical fertilizers and pesticides used in Indonesia. These chemicals can increase plant lead (Pb) accumulation and affect other organisms through its circulation with food chain. Excess amounts of Pb in soil may be remediated using different approaches such as bioremediation. Rhizosphere bacteria can be used as bioremediation agents to reduce Pb accumulation in plants and also increase plant growth. Actinomycetes, Azotobacter sp., Azospirillum sp., Rhizobium sp., Pseudomonas sp., Lactobacillus sp., Bacillus sp., and Streptomyces sp. are some of the several bacteria that can reduce lead (Pb) accumulation in plants by the ability to sequester Pb, change its oxidation state, or enable Pb to precipitate. This research was conducted to determine the ability of the rhizosphere bacterial consortium to prevent lead (Pb) accumulation in rice plants. This study confirmed that the application of rhizosphere bacterial consortium to rice plants contaminated with lead (Pb) can reduce the plant's lead (Pb) content by up to 45%. The use of a bacterial consortium did not significantly affect the growth parameters of the plant but increased root length by 41%, fresh weight by 32%, dry weight by 26%, and chlorophyll content by 25%, in rice plants contaminated with Pb.